A Review Of Athletes Motivation To Participate In Training at Jambi City Athletics Clubs - Dosmauli Sianturi; Sukendro; Bangkit Yudho Prabowo (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to determine the level of motivation of athletes participating in training at the Jambi City Athletic Club. This research is a quantitative descriptive research with a survey method. The population in this study amounted to 150 athletes from 3 athletic clubs in the city of Jambi, the sample in this study amounted to 30 athletes aged 12-15 years who were members of 3 athletic clubs in the city of Jambi. The sampling technique used is purposive sampling. The research instrument used a likert scale questionnaire consisting of indicators of intrinsic motivation (interest and desire to achieve) and extrinsic motivation (training methods, trainers, facilities and infrastructure and environment). The data analysis technique uses descriptive analysis in the form of percentages. The results of the data calculation show that the level of motivation of athletes of the Jambi City Athletic Club aged 12-15 years obtained an average score of 84.85 and is included in the very high category. The results of the study on intrinsic motivation obtained a very high category of 56.7% and extrinsic motivation obtained a high category of 53.3%. Intrinsic motivation has a more dominant percentage compared to extrinsic motivation.